A genetic register for von Hippel-Lindau disease. Issue 2 (February 1996) - Maddock, I R; Moran, A; Maher, E R; Teare, M D; Norman, A; Payne, S J; Whitehouse, R; Dodd, C; Lavin, M; Hartley, N; Super, M; Evans, D G
Abstract : A genetic register for von Hippel-Lindau disease was set up in the north west of England in 1990. Population statistics, clinical features, age at onset, and survival of 83 people affected with von Hippel-Lindau (VHL) disease were studied. In addition, the effectiveness of the screening programme used and the occurrence of central nervous system haemangioblastomas in the general population were examined. The diagnostic point prevalence of heterozygotes in the North Western Region was 1 center dot 18/100 000 (1/85 000) people, with an estimated birth incidence of 2 center dot 20/100 000 (1/45 500) live births. The mutation rate was estimated directly to be 1 center dot 4 x 10(-6)/gene/generation (1/714 200). The mean age at onset of first symptoms was 26 center dot 25 years, with cerebellar haemangioblastoma being the most common presenting manifestation (34 center dot 9% of cases). The mean age at diagnosis of VHL disease was 30 center dot 87 years. Overall, 50 patients (60 center dot 2%) developed a cerebellar haemangioblastoma, 34 (41 center dot 0%) a retinal angioma, 21 (25 center dot 3%) a renal cell carcinoma, 12 (14 center dot 5%) a spinal haemangioblastoma, and 12 (14 center dot 5%) a phaeochromocytoma. Mean age at diagnosis of renal cell carcinoma (38 center dot 9 years) was significantly higher than that for cerebellar haemangioblastoma (30 center dot 0 years) and retinal angioma (21.1 years). Mean age at death was 40 center dot 9 years with cerebellar haemangioblastoma being the most common cause (47 center dot 7% of deaths). A total of 65 VHL manifestations were diagnosed asymptomatically following appropriate clinical and radiological screening tests, and failure to detect manifestations of VHL disease in spite of appropriate screening occurred on only two occasions. The use of DNA linkage analysis and direct mutation testing reduced the personal risk of carrying the VHL gene to below 1% in 14 people. In addition to the 83 clinically affected subjects, three obligate carriers who were considered to be lesion free in spite of extensive screening tests were identified. Fourteen percent of all CNS haemangioblastomas on the regionally based Cancer Registry were found to occur as part of VHL disease, but investigations for VHL in apparently sporadic disease appeared to be limited.